Cognitive-dialectical principles of the study of Turkic languages - Orazaliyeva Эльмира (Turkic Studies Journal, 2021)
Theoretical and applied principles of cognitive Kazakh linguistics determine both current and current linguistic trends, as well as new conceptual approaches and methodologies. In this regard, it is important to study the principles of interrelation of conceptual and structural approaches in Kazakh linguistic science. The reflection in language of the surrounding reality or the surrounding world, in which the connection of language with thinking is laid, determined the anthropocentric nature of modern linguistics. Thus, the analysis of language units as a dialectical-dynamic phenomenon allows us to determine the linguistic and conceptual picture of the world of the Kazakh people, reveal the features of their ethnic mentality and mentality, and lay the Foundation for the conceptual base of the study of the Turkic languages as a whole. As a result, the conceptual methodology proved to be very fruitful for significant diachronic and synchronic studies not only for the Kazakh language, but also for other Turkic languages. The conceptual and cognitive theory of language cognition began to form in Kazakh linguistics in the 20-30s of the XX century at the intersection of language, philosophy, and psychology, and it is closely related to the comparative and structural approaches to the knowledge of human existence, the connection of language with thinking. The smooth transition of structural principles into the element of philosophical, logical and cognitive directions became the basis for semantic research in the modern Kazakh language. The article reveals the conceptual and structural connections of the Kazakh language through the analysis of language units extracted from the research of Kazakh scientists in diachrony and synchrony.